Functional Relationships Between Fertility and Some Soil Parameters - EKBERLI*, IMANVERDI; KERIMOVA†, ELLADA (Asian Journal of Chemistry, 2010)
The importance of empirical and theoretical model derivation in agriculture has been increased due to presence of overwhelming data obtained from researches in soil science and extensive usage of computer in Agriculture. Mathematical definition of fertility is significantly related to research of ecological fertility, usage of maximum parameter values, management and prediction of fertility. The derivation of mathematical models and their application after execution of field and laboratory studies are important steps in comprehending soil fertility. Some agroecological, agrophysical and agrochemical characteristics of soils that constitute conceptual soil model are taken into account in the field and laboratory studies in order to obtain fertility model for irrigated gray-meadow soils. These parameters were determined, evaluated and studied based on the field experiments. The relationships between the parameters and productivity of cotton were found out and static models were derived by using the least square methods. The correlation coefficients (average R = 0.90) of these models with multiple parameters came out to be statistically significant. The extreme points of function were calculated in order to obtain maximum level of the product cultivation in theoretical way. The evaluation of fertility level of experimental soils by these empirical models seems to be possible as well.